The European sustainable debt market (ESMA, 2023)
Issuance of sustainable-labelled debt has soared over the last years, benefitting from an increasing investor appetite for financial products that contain a sustainability element. At the same time, research suggests that sustainable-labelled debt issuers may benefit from a pricing advantage, the so-called 'greenium', which is often attributed to investor's willingness to forego returns in exchange for the sustainability element of the financial product they are investing in. However, existing evidence has not been conclusive so far regarding the existence of a definite pricing advantage, and it further focuses mainly on green bonds only. This article expands the analytical work to all environmental, social and governance (ESG) bond types and identifies a set of key factors potentially causing the greenium. The topic is thereby relevant to several of ESMA's mandates. It directly adds to the understanding of investor preferences for sustainable finance, it helps to investigate any pricing distortions between comparable debt instruments that might impact market stability if they unravel, and, finally, it contributes to ESMA's strategic priority of monitoring ESG market developments and assessing new financial instruments. In terms of findings, our analytical results cannot confirm the existence of a systematic and consistent pricing advantage for any ESG bond category. Furthermore, we find that in the past, issuers of ESG bonds benefitted from pricing premiums based on their issuer characteristics and that issuers' public sustainability commitments do not impact the pricing of their bonds. The European sustainable debt market - do issuers benefit from an ESG pricing effect?
10.2856/468709
Keywords: Graue Literatur; Amtliche Publikation; Rentenmarkt; Nachhaltige Kapitalanlage; EU-Staaten; Greenium; financial stability; financial risk; risk management; sustainable finance; sustainable development; claim; green economy; multi-level governance; bond; fixing of prices; European Securities and Markets Authority; EU financial instrument